2019
DOI: 10.1101/822775
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

NADPH and glutathione redox link TCA cycle activity to endoplasmic reticulum stress

Abstract: 1 2 Endoplasmic reticulum (ER) stress is associated with dysregulated metabolism, but little is 3 known about how the ER responds to metabolic activity. Here, working primarily in mouse 4 hepatocytes, we show that decreasing the availability of substrate for the TCA cycle diminished 5 NADPH production and attenuated ER stress in a manner that depended on glutathione 6 oxidation. ER stress was also alleviated by impairing either TCA-dependent NADPH production 7 or Glutathione Reductase. Conversely, stimulating … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 96 publications
(25 reference statements)
2
4
0
Order By: Relevance
“…7D, E). Having previously demonstrated that pharmacological inhibition of PDKs causes ER stress (16), and here showing the same with knockdown (Fig. 7F, G), this represents an appealing-but as yet unproven-pathway linking HNF4a to ER homeostasis.…”
Section: Discussionsupporting
confidence: 78%
See 4 more Smart Citations
“…7D, E). Having previously demonstrated that pharmacological inhibition of PDKs causes ER stress (16), and here showing the same with knockdown (Fig. 7F, G), this represents an appealing-but as yet unproven-pathway linking HNF4a to ER homeostasis.…”
Section: Discussionsupporting
confidence: 78%
“…The other liver-expressed isoform of PDK, Pdk2, was unaffected in both conditions (Figure S4A, B). We have previously demonstrated that attenuation of TCA cycle flux protects hepatocytes from ER stress (16). Consistent with that idea, combined knockdown of Pdk2/4 (Figure S4C) was sufficient to cause ER stress, as seen by upregulation of UPR target genes (Figure 7F, S4D) and splicing of Xbp1 (Figure 7G).…”
Section: Multiple Pathways Link Hnf4a To Er Stress Sensitivitysupporting
confidence: 80%
See 3 more Smart Citations